Perioperative nursing education in Brazil: reviewing the past to survive the future - Rita Catalina Aquino Caregnato; Bárbara Rodrigues Araujo; Juliana Rizzo Gnatta; Vanessa de Brito Poveda (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to summarize historical aspects related to perioperative nursing education in Brazil and to outline future perspectives. Methods: a descriptive-reflexive essay about the historical process of Brazilian perioperative teaching at undergraduate and graduate levels. Results: the reflection addresses the historical axes of perioperative nursing, teaching perioperative nursing, curriculum changes, graduate studies and relationship with the perioperative period and trends in perioperative nursing education. Curriculum changes reduced time available for teaching and learning, with a focus on the perioperative period, and diluted contents of surgical nursing in other subjects, which could cause irreversible losses for generalist nurses’ training. Final Considerations: when reviewing historical aspects of national nursing curricula, it was found that the nomenclature perioperative nursing was never used in the curriculum, however, the surgical area has always been contemplated in undergraduate and graduate studies. Future trends indicate the need to integrate themes and prepare professionals with perspectives focused on global health and technology.